NILAI CINTA KASIH DALAM NOVEL RINAI KABUT SINGGALANG KARYA MUHAMMAD SUBHAN DAN IMPLIKASINYA DALAM PEMBELAJARAN TEKS NOVEL - Indah Rahayu (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe and analyze the intrinsic elements, the values of love in the novel Rinai Kabut Singgalang by Muhammad Subhan, and their implications in the study of novel texts. This type of research is a qualitative research with descriptive methods. The data in this study are words, phrases and sentences in the novel Rinai Kabut Singgalang by Muhammad Subhan relating to the value of love. Data analysis techniques in this study, namely the collected data were identified, then inventory data, classify data, interpret data, and draw conclusions. Based on the results of the study, found the value of love in the novel Rinai Kabut Singgalang by Muhammad Subhan and its implications in the study of novel texts. First, the value of love for God, with indicators of carrying out obligations as Muslims, avoiding the prohibition of Allah, and always remembering Allah. Second, the value of love for the family, with indicators to support the family, love children, serve parents, and love one another. Third, the value of love for others, with indicators of doing good to others, helping each other with friends, and loving the opposite sex. Fourth, the value of love for oneself, with indicators of self-preservation, actualization and developing one's potential, as well as being happy and peaceful. Fifth, the implication of the value of love in the novel Rinai Kabut Singgalang by Muhammad Subhan in learning text novels for class XII 2013 curriculum.